Corrigendum to "A Realistic Early-Stage Power Grid Verification Algorithm Based on Hierarchical Constraints" [Jan 12 109-120] - Wang, Yuanzhe; Hu, Xiang; Cheng, Chung-Kuan; Pang, Grantham K. H.; Wong, Ngai (IEEE transactions on computer-aided design of integrated circuits and systems, 2012)
The authors for the above titled paper were incorrectly listed. The correct list of authors is presented here.